Expressions of the Johannine kerygma in John 2:23-5:18: historical, literary, and theological readings from the Colloquium Ioanneum 2017 in Jerusalem - Culpepper, R. Alan; Frey, Jörg (Wissenschaftliche Untersuchungen zum Neuen Testament, 2019)
Cover -- Titel -- Table of Contents -- Foreword -- Abbreviations -- Jean Zumstein: The Revelation Strategy in the Gospel of John 3 and 4 -- Christos Karakolis: The Unfinished Story of Nicodemus: A Reader-Centered Approach -- Jan G. van der Watt: "No One Can See/Enter the Kingdom of God without Being Born from Above" (John 3:3, 5): On the King and Kingdom in John -- William R. G. Loader: John 3:13-15: Re-examining the Exaltation-Glorification-Ascension Nexus in John -- Ruben Zimmermann: Erga and Ethics in the Fourth Gospel (John 3:19-21) -- Jörg Frey: Baptism in the Fourth Gospel, and Jesus and John as Baptizers: Historical and Theological Reflections on John 3:22-30 -- Catrin H. Williams: Samaritan Hopes and Scriptural Promises: Engagement with Samaritans and Samaritan Issues in John 4 -- Udo Schnelle: Lokal und Universal: Joh 4,4-42 als Lokaltradition und universales Programm -- Michael Theobald: 2Kön 17,24-41 als Prätext des Gesprächs Jesu mit der Samaritanerin (Joh 4,4-26) -- Adele Reinhartz: Of Mountains and Messiahs: John 4:19-23 and Divine Covenant -- R. Alan Culpepper: John 4:35-38: Harvest Proverbs in the Context of John's Mission Theology -- D. François Tolmie: The Characterisation of the Royal Official in the Fourth Gospel -- Craig R. Koester: The Healing at the Pool of Bethesda (John 5:1-18): A Study in Light of the Archaeological Evidence from Bethesda, Jewish and Greco-Roman Practice, and Johannine Narrative -- Bibliography -- List of Contributors -- Index of Ancient Sources -- Index of Modern Authors.